Competition Determinants of Eurasian Economic Union Oil and Gas Companies - Damira, Aubakirova; Narimanovna, Jaxybekova Galiya; Lyazzat, Yespergenova; Rustamov, Bezhan; Faizulayev, Alimshan; Bekun, Festus Victor (International Journal of Energy Economics and Policy, 2022)
The present study examines the competition determinants of Eurasian Union oil and gas companies for the period of 2012–2020. The study covers a total of 24,813 firm-year observations. This study applied the GMM two-step estimation to capture the endogeneity problem. Our results reveal that leverage, profitability, and efficiency are the main competition determinants. In the Eurasian Union, large oil and gas companies are less competitive. It may be caused by higher corporate bureaucracy and high transaction costs. Oil and gas companies with an efficient level of sales are more competitive in the market. Also, the increase in leverage provides a tax shelter. The price cost margin, the Boone Indicator, and the firm’s income total income ratio are confirmed as efficient competition indicators.